Your body is your barbell no gym. Just gravity. Build a leaner, stronger, more muscular you in 28 days! - Gaddour, B.J (Rodale, 2014)
Torch body fat and build muscle anywhere. Using your body as your barbell, you'll save money, time, and the hassle of going to a gym. This book, from the king of metabolic training, B.J. Gaddour, shows you how to master 8 critical fitness moves--the Bodyweight 8--and use them to achieve the strength, power, endurance, and mobility of an elite athlete